2022
DOI: 10.1002/cia2.12230
|View full text |Cite
|
Sign up to set email alerts
|

New insight of itch mediators and proinflammatory cytokines in epidermolysis bullosa

Abstract: Objectives Epidermolysis bullosa (EB) is a hereditary disorder characterized by mechanical stress‐induced blistering. The presence of extracutaneous complications such as cardiomyopathy and renal disease observed in severe EB subtypes and the fact that pruritus is a common symptom across all EB subtypes indicate that EB is not only a skin fragility disease but also a systemic inflammatory disorder. Our study aims to elucidate the basis of the systemic inflammation seen in EB patients. Methods We analyzed serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“… 10 There is evidence that sera of EB patients contain higher level of itch mediators particularly thymic stromal lymphopoietin (TSLP), interleukin (IL-6) and IFN-γ. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 10 There is evidence that sera of EB patients contain higher level of itch mediators particularly thymic stromal lymphopoietin (TSLP), interleukin (IL-6) and IFN-γ. 11 …”
Section: Discussionmentioning
confidence: 99%
“…2 Several studies have reported that serum IL-6 levels are higher in Dystrophic Epidermolysis Bullosa patients than in healthy controls. 4 IL-6 induces systemic inflammation and acute-phase protein production. 5 This case, possibly the first of its kind to be treated with tocilizumab, emphasizes the role of IL-6 in inflammatory responses in severe forms of EB 5 and its association with recurrent fever in EB patients.…”
Section: Successful Treatment Of Multicentric Castleman's Disease Ass...mentioning
confidence: 99%